Communication and power in the global era : orders and borders - Kraidy, Marwan M., 1972- (New York : Routledge, 2013)
"This book re-visits how we think about communication and power in the global era. It takes stock of the last fifty years of scholarship, maps key patterns and concepts and sets an agenda for theory and research. The book addresses such questions as:How are national and cultural identities re-fashioned and expressed in the global era?How can we best understand the emergence of multiple and sometimes antagonistic modernities worldwide?How are political struggles fought and communicated on the local-national-global nexus? How do we integrate emerging media environments in global communication studies?Bringing together essays from a range of internationally renowned scholars, this book will be useful to undergraduate and postgraduate students on Media and Communication Studies courses, particularly those studying globalisation and global media.Contributors: Hector Amaya Paula Chakravartty Andrew Crocco Myria Georgiou Le Han Anikó Imre Koichi Iwabuchi Marwan M. Kraidy Sara Mourad Patrick D. Murphy Tarik Sabry Paddy Scannell Piotr M. Szpunar Guobin Yang Barbie Zelizer "--
pt. I. Ordering borders : the transnational management of subjectivity -- pt. II. Branding nations : re-imagining communities in neo-liberal states -- pt. III. Being modern : situating the grand narrative -- pt. IV. Destabilizing orders : resistance and social transformation.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Communication, International; Mass media and globalization; Mass media -- Social aspects; Mass media -- Political aspects; Electronic books